Long-term outcome of fusion for degenerative disc disease in the lumbar spine. (December 2019) - Endler, Peter; Ekman, Per; Berglund, Ivan; Möller, Hans; Gerdhem, Paul
Abstract : Aims: Chronic low back pain due to degenerative disc disease is sometimes treated with fusion. We compared the outcome of three different fusion techniques in the Swedish Spine Register: noninstrumented posterolateral fusion (PLF), instrumented posterolateral fusion (IPLF), and interbody fusion (IBF). Patients and Methods: A total of 2874 patients who were operated on at one or two lumbar levels were followed for a mean of 9.2 years (3.6 to 19.1) for any additional lumbar spine surgery. Patient-reported outcome data were available preoperatively (n = 2874) and at one year (n = 2274), two years (n = 1958), and a mean of 6.9 years (n = 1518) postoperatively and consisted of global assessment and visual analogue scales of leg and back pain, Oswestry Disability Index, EuroQol five-dimensional index, 36-Item Short-Form Health Survey, and satisfaction with treatment. Statistical analyses were performed with competing-risks proportional hazards regression or analysis of covariance, adjusted for baseline variables. Results: The number of patients with additional surgery were 32/183 (17%) in the PLF group, 229/1256 (18%) in the IPLF group, and 439/1435 (31%) in the IBF group. With the PLF group as a reference, the hazard ratio for additional lumbar surgery was 1.16 (95% confidence interval (CI) 0.78 to 1.72) for the IPLF group and 2.13 (95% CI 1.45 to 3.12) for the IBF group. All patient-reported outcomes improved after surgery (p < 0.001) but were without statistically significant differences between the groups at the one-, two- and 6.9-year follow-ups (all p ≥ 0.12). Conclusion: The addition of interbody fusion to posterolateral fusion was associated with a higher risk for additional surgery and showed no advantages in patient-reported outcome Cite this article: Bone Joint J 2019;101-B:1526–1533